Colágeno: caracteristicas químicas e propriedades funcionais - Silva, Tatiane Ferreira da [UNESP]; Penna, Ana Lúcia Barretto [UNESP] (My University, 2012)
Many types of food contain ingredients or bioactive compounds that provide health benefits. The collagen is a fibrous protein found in the connective tissue of the body, and it plays a part in the tissues resistance and elasticity. Due to their functional characteristics, this protein has been added into foods in order to achieve therapeutic effects. This paper aimed at showing how the collagen formation occurs, and the beneficial effects of this compound in the organism as well as its characteristics, properties and applications in food.

Muitos alimentos possuem ingredientes ou compostos bioativos que oferecem benefícios à saúde. O colágeno, que é uma proteína fibrosa encontrada nos tecidos conjuntivos do corpo, tem a função de contribuir com a resistência e elasticidade dos tecidos. Em virtude de suas características funcionais, essa proteína tem sido adicionada aos alimentos com o intuito de alcançar os efeitos terapêuticos. O presente trabalho visa mostrar como ocorre a formação do colágeno e os efeitos benéficos no organismo, bem como as características, propriedades e aplicações em alimentos.
Chemical characteristics and functional properties of collagen
Keywords: propriedade funcional; suplemento alimentar; composto bioativo; functional property; food supplement; bioactive compound